Site-specific nutrient management: impact on productivity, nutrient uptake and economics of rice-wheat system - U P SHAHI; V K SINGH; ABHINAV KUMAR; P K UPADHYAY; P K RAI (The Indian Journal of Agricultural Sciences, 2022)
A field experiment was conducted on Typic Ustochrept soil at the Crop Research Centre of Sardar Vallabhbhai Patel University of Agriculture and Technology, Meerut, for two years (2014–15 to 2015–16) to evaluate site specific nutrient management (SSNM) against state recommendation (SR), integration of SSNM and SR with crop residue and farm yard manure. In terms of crop growth yield, nutrient uptake and economics, SSNM had significantly higher growth parameters, viz. number of tillers/m2 and dry matter accumulation as compared to SR in both rice and wheat crops. Different yield attributes, viz. number of grains/panicle or spike, test weight of rice and wheat were also higher with SSNM. SSNM out yielded for rice, wheat and rice-wheat system (RWS) productivity by 10.3%, 14.1% and 11.9%. System N, P and K uptake under SSNM was also higher by 24.36, 9.55 and 36.01 kg/ha, respectively, compared to SR. An additional income of `12953/ha over SR and maximum return/rupee invested (`2.50) was also recorded with SSNM. Recycling of 5 t/ha rice and wheat straw residue along with SSNM had added advantage.